An argument for ontological nihilism - Westerhoff, J (Routledge, 2021)
This paper has two main aims. I first argue that ontological nihilism, that is, the view that there are no things is a consistent position. Second, I discuss an argument for the view that nihilism is not just possible but actually true, that is that there actually are no things (This paper is not meant as an addition to the considerable literature on the question of why there is something rather than nothing. Of course, any attempt to answer this question would have to presuppose the conclusion of the first section, that is, that nihilism is a consistent position. But if the argument in the second section goes through the question we would then have to answer is not why there is something rather than nothing, but why there is nothing rather than something). My argument is based on two main premisses, eliminativism (‘only the fundamental exists’) and non-foundationalism (‘it’s dependence all the way down’) which jointly entail ontological nihilism. I conclude with some reflections on the consequences of the nihilist position for the project of constructing a fundamental metaphysical theory.